BIMBINGAN DAN SELF MANAGEMENT SANTRIWATI PENGHAFAL AL-QUR’AN - Hanik Mufaridah; Fitriatul Hasanah (Fakultas Dakwah Universitas Ibrahimy, 2022)
The Qur’an is the first and foremost source of Islamic teachings. It is an obligation for all Muslims to practice and maintain the purity of the Qur’an. One of the efforts to maintain the purity of the Qur’an is to memorize it. In memorizing the female students, of course, have difficulties in achieving the memorization target that has been programmed by the Tahfidzul Qur’an Dormitory. With that, the female students need guidance and self-management to complete the target of memorizing the Qur’an. This study aims to: (1) find out how the guidance is given to female students who memorize the Qur’an (2) find out how self-management of female students who memorize the Qur’an in the Tahfidzul Qur’an Dormitory Islamic Boarding School Salafiyah Syafi’iyah Sukorejo Situbondo. This research is a qualitative research method with the type of case study research by taking the background of a dormitory that has a tahfidz institution and the subjects are BK teachers or supervisors and tahfidz students. Data was collected by conducting observations, interviews and documentation. Data analysis is carried out by giving meaning to the data that has been collected, and from that meaning conclusions are drawn. The results of this study show (1) the guidance used by BK teachers and supervisors in the tahfidzul Qur’an dormitory of the Salafiyah Syafi’iyah Islamic Boarding School Sukorejo Situbondo. Counseling teachers and supervisors use two kinds of guidance, namely individual and group guidance. (2) Self management owned by female students who memorized the Qur’an in helping to complete the memorization target that had been programmed by self-management owned by the students, namely time management, small notes, tawassul, taqwiyatul hifdzi prayer, lots of reciting, self-control, and so on.